Drug preparation, injection-related infections, and harm reduction practices among a national sample of individuals entering treatment for opioid use disorder - Laura R. Marks; Michael J. Durkin; Kelly Ayres; Matthew Ellis (BMC, 2024)
Abstract Background The rise in injection drug use in the USA has led to an increase in injection site infections. We performed a national survey of people who use drugs to evaluate common drug use preparation, harm reduction practices, and experiences with injection site infections. Methods A survey was disseminated to members of the Survey of Key Informants' Patients Program from 2021 to 2022 and distributed to patients 18 years or older newly entering one of 68 substance use disorder treatment programs across the USA with a primary diagnosis of an opioid use disorder. Participants were surveyed about practices when preparing and using drugs, along with self-reported infections and drug use complications. Results 1289 participants responded to the survey. Sexually transmitted infections were common, with 37.6% reporting ever having had any sexually transmitted infection. Injection-associated infections had affected 63.4% of participants who had ever used injection drugs. Many respondents reported not seeking professional medical assistance for infection management, including 29% draining abscesses without seeking medical care and 22.8% obtaining antibiotics through non-healthcare sources. Non-sterile injection practices included sharing needles with others who were febrile or ill (18%), using needles previously used to drain wounds/abscesses (9.9%) for subsequent injection drug use, and licking needles (21.2%). Conclusion Patients entering treatment for opioid use disorder reported a high burden of infectious diseases. A number of easily-modifiable high risk behaviors for developing injection-related infections were identified. Efforts are needed to disseminate targeted harm reduction education to PWID on how to reduce their risks for injection-related infections.